Prioritizing Health Care Workers Safety: The International Year of Health and Care Workers 2021 - Evy Yunihastuti (Acta Medica Indonesiana, 2022)
Healthcare workers pose a substantial risk of acquiring COVID-19 infection during their daily works. We have seen various conditions during the pandemic, such as limited adequate personal protective equipment (PPE), accurate diagnostic tests, lack of information regarding disease management, unsupportive work environment, and excessive workload, increased the number of HCWs-infected COVID-19. Compared to the general population, the risk of COVID-19 infection was several-fold higher in HCWs.